Phraseological semantics through the prism of cognitive linguistics - Alshynbekova М.С.; Zhumanbekova Н.З. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
Currently phraseology is one of the most relevant branches of linguistics. Today, phraseology is one of the most important branches of linguistics. This article will address the current problems of domestic and foreign phraseology and the scientific results will be analyzed. Despite numerous studies in the field of comparative phraseology, the semantics of phraseological units is studied in a new aspect of cognitive phraseology and contributes to the further development of this direction. The priority tasks of the modern stage of linguoculturological research of phraseology include the development of methods that make it possible to identify and grasp new areas of interaction between phraseology and culture. The relevancy consists in developing methods that allow comparative studies of phraseological units of different languages and methods aimed at discovering the universal and distinctive features of creating phraseological signs imparted to such units by one or another national culture. The semantic structure of phraseological units as a complex multidimensional system requires complex analysis. The multidimensional nature of meanings often implies solving the problem of the complex nature of their semantics, which is reflected in the interaction of the symbolic function of phraseology and the information provided by each macrocomponent of the semantic structure. Especially relevant is the study of the process of the emergence of a new semantics of phraseology, known as phraseologization. The article reviews the study of the process of phraseologization, demonstrates the dynamic aspect of phraseology and systematizes the main directions of this process.